Evaluating the Numeracy Cognitive Level of Indonesian Elementary School Students using the Minimum Competency Assessment - Asnawati, Rini; Widyastuti, Widyastuti; Maulina, Dina; Anggoro, Bambang Sri; Ferdiansyah, Muhammad; Izzati, Nurma (FKIP Universitas Lampung, 2022)
This study aims to describe the achievement of the numeracy cognitive level of elementary school students on a minimum competency assessment. The population of this study were fifth grade students at C-accredited elementary school in Lampung province. The sample of this study selected using stratified random sampling. Data were collected using a level 2 numeracy test instrument developed by the Center for Evaluation and Learning of the Ministry of Education and Culture of the Republic of Indonesia. Data were analyzed descriptively and inferentially using the Mann-Whitney test. It was concluded that: a) students’ category of numeracy ability was “competent” (mean score 43.04); b) there is no significant difference between the numeracy abilities of male and female students; c) the highest percentage of correct answers was matching type questions (62.9%); and d) the lowest cognitive level was achieved is in the measurement concept which was only 28.6. Keywords: elementary school students, minimum competency assessment, numeracy cognitive level. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp428-436